CĂTĂLIN NICOLAE POPA, SIMON STODDART (EDS.), FINGERPRINTING THE IRON AGE. APPROACHES TO IDENTITY IN THE EUROPEAN IRON AGE – INTEGRATING SOUTH-EASTERN EUROPE INTO THE DEBATE, OXFORD – PHILADELPHIA, OXBOW BOOKS, 2014, 428 PP., ISBN 978-1-78297-675-2 - Hent Alin (Journal of Ancient History and Archaeology, 2015)
Cătălin Nicolae Popa, Simon Stoddart (eds.), Fingerprinting the Iron Age. Approaches to Identity in the European Iron Age – Integrating South-Eastern Europe into the Debate, Oxford – Philadelphia, Oxbow Books, 2014, 428 pp., ISBN 978-1- 78297-675-2